2006
DOI: 10.1021/jp061620a
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Phase Transition Induced by Pressure in LiOH·H2O

Abstract: When the free energy surface of the lithium hydroxide monohydrate crystal was explored, the high-pressure solid-state phase transition was determined. The high-pressure phase has been obtained through ab initio Car-Parrinello molecular dynamics simulation in the isothermic-isobaric ensemble. The recent metadynamics method has been applied to overcome the high activation energy barriers typical of rare events, like solid-state phase transition at high pressures. In the LiOH x H2O system, there are two kinds of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
7
1
Order By: Relevance
“…The isotopic spectra 7, 9 also show a marked dependence on both 6 Li/ 7 Li and H/D substitution indicating that coupling is present, in contradiction to the conclusions of Di Petro et al 8 This is also demonstrated by setting the cross section of all the atoms in the unit cell to zero except for the species of interest, thus only motions involving these entities will contribute to the INS spectrum so generated. This is indicated by the continuous intensity between 90 and 500 cm −1 in the experimental INS spectrum, indicating that the modes are dispersed.…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…The isotopic spectra 7, 9 also show a marked dependence on both 6 Li/ 7 Li and H/D substitution indicating that coupling is present, in contradiction to the conclusions of Di Petro et al 8 This is also demonstrated by setting the cross section of all the atoms in the unit cell to zero except for the species of interest, thus only motions involving these entities will contribute to the INS spectrum so generated. This is indicated by the continuous intensity between 90 and 500 cm −1 in the experimental INS spectrum, indicating that the modes are dispersed.…”
Section: Discussioncontrasting
confidence: 67%
“…17,18 Table II compares geometric parameters for the structure optimized at the experimental lattice parameters and also for where both geometry and lattice optimization have been carried out. 8 The results clearly show that the expectation of rock > wag > twist is incorrect; the twist and wag are at similar frequencies with a small factor group splitting. The intramolecular bond distances and angles are the same in the two calculations and agree well with experiment (<0.02 Å for distances and 0.5 • for the angle).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations